Comparative Outcomes of a Transthyretin Amyloid Cardiomyopathy Cohort Versus Patients With Heart Failure With Preserved Ejection Fraction Enrolled in the TOPCAT Trial - Morris M. Kim; Mark Prasad; Yunwoo Burton; Clinton M. Kolseth; Yuanzi Zhao; Pranav Chandrashekar; Babak Nazer; Ahmad Masri (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Transthyretin cardiac amyloidosis (ATTR‐CM), found in 6% to 15% of cohorts with heart failure with preserved ejection fraction, has long been considered a rare disease with poor prognosis. New treatments have made it one of the few directly treatable causes of heart failure. This study sought to determine whether patients with ATTR‐CM, particularly those treated with tafamidis, have comparable survival to an unselected cohort with heart failure with preserved ejection fraction. Methods and Results We compared the clinical characteristics and outcomes between a single‐center cohort of patients with ATTR‐CM (n=114) and patients with heart failure with preserved ejection fraction enrolled in the TOPCAT (Treatment of Preserved Cardiac Function Heart Failure With an Aldosterone Antagonist) trial (n=1761, excluding Russia and Georgia). The primary outcome was a composite of all‐cause death, heart failure hospitalization, myocardial infarction, and stroke. Subgroup analysis of patients with ATTR‐CM treated with tafamidis was also performed. Patients with ATTR‐CM had higher rates of the primary composite outcome compared with patients enrolled in the TOPCAT trial (hazard ratio [HR], 1.44 [95% CI, 1.09–1.91]; P=0.01), with similar rates of all‐cause death (HR, 1.43 [95% CI, 0.99–2.06]; P=0.06) but higher rates of heart failure hospitalizations (HR, 1.62 [95% CI, 1.15–2.28]; P<0.01). Compared with patients enrolled in TOPCAT, patients with ATTR‐CM treated with tafamidis had similar rates of the primary composite outcome (HR, 1.30 [95% CI, 0.86–1.96]; P=0.21) and all‐cause death (HR, 1.10 [95% CI, 0.57–2.14]; P=0.78) but higher rates of heart failure hospitalizations (HR, 1.96 [95% CI, 1.27–3.02]; P<0.01). Conclusions Patients with ATTR‐CM treated with tafamidis have similar rates of all‐cause death compared with patients with heart failure with preserved ejection fraction, with higher rates of heart failure hospitalizations.